Cellular Pathogenesis of Chemotherapy-Induced Peripheral Neuropathy: Insights From Drosophila and Human-Engineered Skin Models - Shin, Grace Ji-eun; Abaci, Hasan Erbil; Smith, Madison Christine (Frontiers in Pain Research, 2022)
Chemotherapy-induced peripheral neuropathy (CIPN) is a highly prevalent and complex condition arising from chemotherapy cancer treatments. Currently, there are no treatment or prevention options in the clinic. CIPN accompanies pain-related sensory functions starting from the hands and feet. Studies focusing on neurons in vitro and in vivo models significantly advanced our understanding of CIPN pathological mechanisms. However, given the direct toxicity shown in both neurons and non-neuronal cells, effective in vivo or in vitro models that allow the investigation of neurons in their local environment are required. No single model can provide a complete solution for the required investigation, therefore, utilizing a multi-model approach would allow complementary advantages of different models and robustly validate findings before further translation. This review aims first to summarize approaches and insights from CIPN in vivo models utilizing small model organisms. We will focus on Drosophila melanogaster CIPN models that are genetically amenable and accessible to study neuronal interactions with the local environment in vivo. Second, we will discuss how these findings could be tested in physiologically relevant vertebrate models. We will focus on in vitro approaches using human cells and summarize the current understanding of engineering approaches that may allow the investigation of pathological changes in neurons and the skin environment.